2019
DOI: 10.1002/pssa.201900392
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Affinity of Metal Electrodes as Control Parameter in Tuning the Performance of CuxO‐Based Resistive Random Access Memory Devices

Abstract: Cu x O-based resistive random access memory (RRAM) devices are fabricated with low, medium, and high oxygen affinity metals as the top electrode and gold and platinum as the bottom electrode. Switching performance of the device with varying oxygen affinity is observed. The variation, mean, and the cycle percentage of V set and V reset values decrease with the decrease in oxygen affinity but increase in the case of I reset . The reset power parameter decreases with oxygen affinity of metal electrodes (OAME). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…With this TiOx oxygen reservoir, the formation of oxygen vacancies in the vicinity of ZrO 2−x /TiO 2 interface will become more beneficial for further improvement in the resistive switching characteristics. Previously reported that metal electrodes with high oxygen affinity can easily cause the interface layer to react with oxide film and the migration of oxygen ions between the interface layer and oxide film is a key for inducing the resistive switching characteristics [23,24].…”
Section: Density Functional Theory (Dft) Calculationsmentioning
confidence: 99%
“…With this TiOx oxygen reservoir, the formation of oxygen vacancies in the vicinity of ZrO 2−x /TiO 2 interface will become more beneficial for further improvement in the resistive switching characteristics. Previously reported that metal electrodes with high oxygen affinity can easily cause the interface layer to react with oxide film and the migration of oxygen ions between the interface layer and oxide film is a key for inducing the resistive switching characteristics [23,24].…”
Section: Density Functional Theory (Dft) Calculationsmentioning
confidence: 99%
“…The migration of ions is attributed to the rise in current and attributed to the LRS state. In contrast, reversing the direction of the field results in the formation of an oxide insulating layer because of oxygen ions, reacting with the top Cu electrode at the interface, thus lowering the current, referred to as the HRS state. …”
Section: Methodsmentioning
confidence: 99%